2018
DOI: 10.1002/jpen.1138
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Postnatal Growth Trajectories for Preterm Infants

Abstract: GVA provides an evidence-based approach for individualized growth trajectories. GVA is based on physiologic data and that healthy preterm infants adjust their postnatal trajectory below their birth percentile. GVA may reflect a biologic principle because it matches consistently with WHOGS at 42+0/7 weeks for all preterm infants from 24 to 34 weeks. This concept could become a bedside tool to aid clinicians in monitoring growth, guiding nutrition, and minimizing chronic adult disease risks as a consequence of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…The clinical value of FBA is twofold. First, tracking of individual growth trajectories is becoming an important part of individualized medicine for preterm infants (58)(59)(60). Tracking…”
Section: Discussionmentioning
confidence: 99%
“…The clinical value of FBA is twofold. First, tracking of individual growth trajectories is becoming an important part of individualized medicine for preterm infants (58)(59)(60). Tracking…”
Section: Discussionmentioning
confidence: 99%
“…However, this long duration of measurement is difficult to translate to shorter durations of growth velocity measurement as needed for clinical care decisions during hospitalization. Other innovative measures such as weight gain ratios [ 23 ] or growth velocity calculations with postnatal adjustment are relatively new methods for preterm infant growth monitoring and, therefore, require further investigation as methods to control for the errors in preterm infant growth assessment [ 23 , 26 ]. In our study, the HGQ demonstrated significantly higher growth velocity when compared to the LGQ group.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size required to compare two means in two-sided equality test was estimated based on results from a prior double blind, randomized clinical trial, investigating the effect of TG vs SF of breast milk on the changes of anthropometric parameters and body composition in preterm children [ 23 , 24 ]. It was determined that a mean difference of weight gain 1.9 g/kg/day between groups would be clinically important and feasible during intervention.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%